Safety and Efficacy of Charakokta Raktapachak Yoga in Patients of Urticaria (Kotha) Caused Due to Dooshivisha – A Randomized Controlled Trial: Pharmaceutical sciences-Pharmacology - Suryakant, Kakde Suvarna; Smita, Patil; Gupta, Rajkumar; Suryakant, kakde Pravin (International Journal of Life Science and Pharma Research, 2024)
This controlled clinical study aimed to assess the safety and efficacy of Charkokta Raktapachak Yoga in treating DooshivishajanyaKotha (urticaria), a condition known for its challenging recurrence. Two groups, each comprising 30 patients, were formed: a standard groupreceiving Tab. Cetrizine 10mg OD, and an experimental group receiving Tab. Raktapchak Yoga 500mg/day in two divided doses for 42 days.Follow-ups occurred every 7 days. The study evaluated manifestations such as raised edematous swelling (kotha), itching (kandu), burningsensation (daha), and pricking sensation (toda). Objective parameters like Hb, ESR, AEC, and stool examination were assessed before andafter the study. Statistical analysis revealed significant inter-group differences after treatment for urticaria (p = 0.0047), itching (p < 0.0001),pricking sensation (p = 0.0025), and burning sensation (p = 0.0018). In the experimental group, significant improvements were observed inobjective parameters: hemoglobin levels (p = 0.0026), ESR (p < 0.0001), AEC levels (p < 0.0001), and stool examination (p = 0.0176).Symptoms such as the urticarial wheel, itching, pricking, and burning sensation were alleviated more in the experimental group than in thecontrol group. Recurrence of symptoms was reduced in the experimental group post-treatment compared to the standard group. Objectiveparameters improved in the experimental group, affirms the safety and efficacy of Charkokta Raktapachak Yoga in treating urticaria caused byDooshivisha.